Physical Activity and Body Mass Index: The Contribution of Age and Workplace Characteristics - Nelson, Candace C. (2014)
BACKGROUND: The workplace is an important domain for adults, and many effective interventions targeting physical activity and weight reduction have been implemented in the workplace. However, the U.S. workforce is aging and few studies have examined the relationship of BMI, physical activity, and age as they relate to workplace characteristics. PURPOSE: This paper reports on the distribution of physical activity and BMI by age in a population of hospital-based healthcare workers and investigates the relationships among workplace characteristics, physical activity, and BMI. METHODS: Data from a survey of patient care workers in two large academic hospitals in the Boston area were collected in late 2009 and analyzed in early 2013. RESULTS: In multivariate models, workers reporting greater decision latitude (OR=1.02; 95% CI=1.01, 1.03) and job flexibility (OR=1.05; 95% CI=1.01, 1.10) reported greater physical activity. Overweight and obesity increased with age (p<0.01), even after adjusting for workplace characteristics. Sleep deficiency (OR=1.56; 95% CI=1.15, 2.12) and workplace harassment (OR= 1.62; 95% CI=1.20, 2.18) were also associated with obesity. CONCLUSIONS: These findings underscore the persistent impact of the work environment for workers of all ages. Based on these results, programs or policies aimed at improving the work environment, especially decision latitude, job flexibility and workplace harassment should be included in the design of worksite-based health promotion interventions targeting physical activity or obesity.